Research of heat capacity of multicomponent carbon-aluminium composition materials - Воденникова, Оксана Сергеевна (Technology audit and production reserves, 2014)
Despite the previously conducted specific thermal researches of one-and two-phase composite materials there are a need for integrated thermal researches for new multicomponent carbon-aluminum composites of different composition and content obtained by hot pressing. This article presents the results of experimental researches of the heat capacity of the samples of carbon-aluminum composite materials of tribotechnical purpose obtained using the comparative method of dynamic calorimeter with a heat meter and adiabatic membrane. The influence of both the component composition and content of the composites on heat capacity indicators is shown. A comparative analysis of the results with previously known heat capacity calculated indicators is conducted. It is shown that the values of maximum deviations between experimental and calculated values are less than 20%. The research results have a scientific and practical interest for the development of new units for dry friction engineering, aviation and space industry.